Kinetics of the partitioning of carbon and substitutional alloying elements during quenching and partitioning (Q&P) processing of medium Mn steel. (1st April 2016) - Seo, Eun Jung; Cho, Lawrence; De Cooman, Bruno C.
Abstract: Quenching and partitioning (Q&P) processing of medium Mn steel is a new approach to produce formable ultra-high strength steel with a martensite + austenite microstructure. Carbon partitioning from martensite into austenite is essential for austenite stabilization during Q&P processing, and substitutional atom partitioning is usually considered not to occur. The present study provides a direct atomic-scale evidence for the partitioning of both interstitial carbon and substitutional Mn and Si, during the Q&P processing of medium Mn steel by means of 3-dimensional atom probe tomography. The experimental results were compared to results of a numerical simulation of the kinetics of carbon, Si and Mn partitioning during Q&P processing assuming an immobile martensite-austenite phase boundary. Both show that short range substitutional alloying element partitioning occurs during the partitioning stage in Q&P processing. Graphical abstract: